Mapping Opinion Networks: An Interaction Network Analysis of Commenters on Narasi Newsroom's "Weda Bay Nickel Downstreaming" YouTube Video - Az-zahra Mutiara Syofi Ramadhina; Lovie Harleyna Murti; Gema Nusantara Bakry (Khazanah Sosial, 2025)
Indonesia is the world's largest producer of nickel reserves. The government has implemented a nickel downstreaming policy to increase the added value of this commodity. One of the centres of nickel downstreaming is Weda Bay in North Maluku, which has recorded significant economic growth. Behind this financial success, nickel downstreaming has harmed social and environmental aspects. These impacts have triggered various responses from the community, many of which have been channelled through social media such as YouTube. This study analyses the network of public opinion in the comments section of the YouTube video “The Curse of Weda Bay Nickel Downstreaming (PART 1)” by Narasi Newsroom using the Social Network Analysis (SNA) method with Gephi 0.10 software and reviews negative, positive, and neutral sentiments using the Naïve Bayes model through Google Colab. The network analysis results show a diameter of 2, density of 0.000 (very low), and modularity of 0.838 (high), indicating that interactions between users are rare and that there are separate communities. Centrality measurements (degree, betweenness, closeness, and eigenvector) show @knowledgeid970 and @kadyrov12373 as the leading and most influential actors in the comment network. Naïve Bayes sentiment analysis shows that 52.49% of comments have negative sentiment, 26.45% are neutral, and only 21.06% are positive. The data needs to be balanced using SMOTE, and more accurate models need to be explored. Negative sentiment is dominated by concerns about environmental impacts such as deforestation, pollution, and pressure on clean water supplies due to nickel downstreaming.